Addenda and corrigenda to A World Catalogue of Families and Genera of Curculionoidea (Insecta: Coleoptera). 2 - Lyal, Christopher H.c.; Alonso-Zarazaga, Miguel A. (Zootaxa, 2006)
Omissions from and corrections to Alonso-Zarazaga & Lyal (1999) and Alonso-Zarazaga & Lyal (2002) are given. The following valid taxon described before 2000 was absent and is now included: Oedeuops Zhang, 1989 (fossil) in Attelabidae. A new replacement name is proposed in Brachyceridae: Brotheusini Alonso-Zarazaga and Lyal, nom. nov., for Brotheini Marshall, 1907, non Simon, 1879 (Scorpiones). New synonymies are: Mecocerini Lacordaire 1866 (= Cappadocini Alonso-Zarazaga & Lyal, 1999, syn. nov.) and Phloeophilus Schoenherr, 1833 (= Cappadox Alonso-Zarazaga & Lyal, 1999, syn. nov. = Platynorhynchus Schoenherr, 1839, syn. nov.) in Anthribidae; Cnemoxys Marshall, 1956 (= Lavabrenymus Hoffmann, 1966, syn. nov.) in Curculionidae Conoderinae. Omitted synonymies are: Otiorhynchus (Thalycrynchus) Reitter, 1912 (= Panaphilis Dejean, 1821) (removed from synonymy with Otiorhynchus s. str) and Brachysomus Schoenherr, 1823 (= Pseudoptochus Formánek, 1905) in Curculionidae Entiminae. A new combination is: Cnemoxys armatus (Hoffmann, 1966) comb. nov. from Lavabrenymus Hoffmann, 1966. New placements are: Alloschema Jordan, 1928 to Zygaenodini (from Cappadocini) (Anthribidae). Diastatotropis Lacordaire, 1866, Systellorhynchus Blanchard, 1849 and Perroudius Holloway, 1982 to Anthribinae incertae sedis (from Cappadocini) (Anthribidae). Eczesaris Pascoe, 1859 and Ethneca Pascoe, 1860 to Mecocerini (from Cappadocini) (Anthribidae). Codmius Faust, 1895 to Conoderinae Campyloscelini Corynemerina (from Baridinae Madarini Tonesiina) (Curculionidae). The subgenera Acercomecus Reitter, 1903, Gnathomecus Reitter, 1903 and Hypesamus Reitter, 1903 are wrongly listed under Esamus Chevrolat, 1880 and should be transferred to be under Megamecus Reitter, 1903.